Features of propagation of droplets of water and special water-based compositions in a sample of forest fuel material; Thermal Science; Vol. 23, iss. 6, pt. A - Antonov D. V. Dmitry Vladimirovich; Zhdanova A. O. Alena Olegovna; Shlegel N. E. Nikita Evgenjevich; Voytkov I. S. Ivan Sergeevich; Osipov K. Yu. Konstantin Yuryevich; Kuznetsov G. V. Geny Vladimirovich; Volkov R. S. Roman Sergeevich (2019, 2019)
Title screen